Sustainable and Ecofriendly Chemical Design of High Performance Bio-Based Thermosets for Advanced Applications - Derradji, Mehdi; Mehelli, Oussama; Liu, Wenbin; Fantuzzi, Nicholas (Frontiers in Chemistry, 2021)
High performance thermosetting resins are targeted in many exigent applications, such as aerospace and marine fields, for the development of lightweight structural composites. Till now, these industries only rely on petroleum-based materials for their supposedly better performances. However, the latest developments in the field suggest otherwise. In fact, many reports confirmed that sustainable and ecofriendly thermosetting polymers can display similar or even better performances. Additionally, exploring alternative renewable feedstock’s to meet the ever increasing demands of these industries is an essential step towards sustainable development. Aiming to unravel the potential of these materials, the present review summarizes the most relevant chemical routes allowing the preparation of fully or partially bio-based thermosetting resins. Meanwhile, the overall performances of these exceptional materials are also compared with their petroleum-based counterparts.